Playing to the camera film actors discuss their craft - Cardullo, Bert; Geduld, Harry; Gottesman, Ronald; Woods, Leigh; Kauffmann, Stanley (New Haven Yale University Press, 1998)
Over the last century, actors from Charlie Chaplin & Lillian Gish to Meryl Streep & Jeff Daniels have spoken about the art & technique of playing to the camera. This is an anthology of their insider observations
Acting for the films in 1912 / Charles Graham -- My autobiography / Charles Chaplin -- The "new art" / E.H. Sothern -- Screen acting / Mae Marsh -- The movies, Mr. Griffith, and me / Lillian Gish -- Dialogue with the actress / Louise Brooks -- The new stage fright : talking pictures / Louise Closer Hale -- Acting in talking pictures / Betty Compson -- What the public wants / Greta Garbo -- My ten years in the studios / George Arliss -- Lorenzo goes to Hollywood / Edward Arnold -- The actor / Lionel Barrymore -- Film acting / Robert Donat -- The film actor / Eric Portman -- Mask or face / Michael Redgrave -- Talking about acting / Albert Finney & Mary Ure -- On acting / Laurence Olivier -- Notes of a Soviet actor / Nikolai K. Cherkasov -- Stanislavsky's system in the cinema / Vsevolod Pudovkin -- Actor's feeling and director's form / Michael Chekhov -- Some notes on acting / Mai Zetterling -- The actor, a witness of his time / Jean-Louis Trintignant -- The game of truth / Marcello Mastroianni -- Conversation with the actress / Liv Ullmann -- Human masks are dangerous / Klaus Maria Brandauer -- The actress plays her part / Bette Davis -- A life on film / Mary Astor -- The player : a profile of an art / Joan Crawford -- Notes on film acting / Hume Cronyn -- The many-splendored actor / James Stewart -- Reflections on forty years of make-believe / Henry Fonda -- Interview with the actress / Gloria Swanson -- Dialogue on screen acting / Katharine Hepburn -- Walking the Hollywood color line / Sidney Poitier -- When women were in the movies / Meryl Streep -- "Commercial" isn't a dirty word, any more than "comedy" / Jeff Daniels -- Conversation with the actor / Jack Lemmon -- The Playboy interview / Marlon Brando -- Dialogue with the actor / Robert De Niro -- Interview with the actor / Dustin Hoffman -- "The bird is on his own" / Jack Nicholson -- "Acting has to be about something else" / Lindsay Crouse.
"Published with assistance from the foundation established in memory of Philip Hamilton McMillan of the class of 1894, Yale College."--Title page verso.
Includes bibliographical references (pages 347-359) and index.
Keywords: Motion picture acting; Motion picture actors and actresses -- Interviews